Rules of Interpretation among Jews: A study extracted from a doctoral dissertation entitled "The Theory of Textual Interpretation in Islam and Judaism" / College of Islamic Sciences / University of Sulaimani - بابكر, محمد; أمين, سامان وهاب (Sulaimani Journal for Humanities, 2025)
Jewish scholars were take care of the interpretation of the old testament, because they made it the sourse of all the things and facts that they face every day.Also, many of old testament Tests are unclear and need interpretation. In addition, there are many events that ocuur and did not mention the torah ruling. The hidtory of interpretation in the jewish religion is ancient and contemporary to the old testament. There is no doubt that jewish scholars have ther rules in the interpretation of the texts, but they did not provide them at the beginning until hillel came and set a basis for an explanation. Then the rabbi Iamial came to thirteen explanatory bases. The influence of Judaism on other religions throughout its long history, in the Islamic era influenced by the approach of Islamic scholars and the science that existed in the Islamic envirment. As well as the impact of the European Renaissance, forcing them to reinterpret many of the texts of the bible.